(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two pesticide field trials were carried out against overwintering San José Scale, Quadraspidiotus perniciosus (Comstock) (Homoptera Diaspididae) on apples (in 2000) and pears (in 2001) in the Emilia-Romagna Region of northern Italy. The active ingredients tested were mineral oil (2.7%), mineral oil and imidacloprid (2.7%), buprofezin added to mineral oil (as a wetting agent) (0.14% + 0.5%), and lime sulphur (25/75): different timings of sprays were also tested. The experimental design consisted of a randomised block with at least four replicates. The efficacy of the treatments (mortality) was estimated by counting scales (dead and alive). Twenty randomly selected infested shoots (1–2 years old) and at least 400 scales were examined from each plot. The results showed that a high level of mortality was caused by all the treatments tested. The choice of which active ingredient used (or mixture thereof) depended on what other pests were present at the time of application (e.g. Dysaphis plantaginea Passerini, Hoplocampa brevis Klug).